2019
DOI: 10.3892/mmr.2019.9858
|View full text |Cite
|
Sign up to set email alerts
|

miR‑671‑3p is downregulated in non‑small cell lung cancer and inhibits cancer progression by directly targeting CCND2

Abstract: MicroRNAs (miRNAs) are implicated in the development and progression of non-small cell lung cancer (NSCLC). A previous study suggested that miR-671-3p suppresses the development of breast cancer. However, the role of miR-671-3p in NSCLC remains largely unknown. In the present study, it was identified that miR-671-3p was significantly upregulated in NSCLC tissues compared with adjacent normal tissues by reverse transcription quantitative polymerase chain reaction (RT-qPCR). Similarly, decreased levels of miR-67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…At the same time, HUANG et al reported that miR-615 inhibits the proliferation and invasion of prostate cancer cells by targeted down-regulation of CCND2. In addition, miR-1297 [32], miR-154, and miR-497 [33] have been reported to target down-regulation of CCND2 to inhibit tumor cell proliferation and migration [34][35][36][37]. For this reason, the present study speculates and…”
Section: Discussionmentioning
confidence: 63%
“…At the same time, HUANG et al reported that miR-615 inhibits the proliferation and invasion of prostate cancer cells by targeted down-regulation of CCND2. In addition, miR-1297 [32], miR-154, and miR-497 [33] have been reported to target down-regulation of CCND2 to inhibit tumor cell proliferation and migration [34][35][36][37]. For this reason, the present study speculates and…”
Section: Discussionmentioning
confidence: 63%
“…The effect of miR-671-3p on tumours is still controversial and mostly based on studies of tumour cells [ 24 , 49 ]. The role of miR-671-3p has not been reported in TME.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of miR-671 has been observed in a panel of human tumors, such as osteosarcoma (23), prostate cancer (24), lung cancer (25), breast cancer (26), and gastric cancer (27). In these tumors, miR-671 was demonstrated to show inhibit the malignant phenotypes of tumor cells by targeting SOX6, CCND2, and FOXM1 (23)(24)(25)(26)(27). However, miR-671 may function as an oncogenic miRNA in other types of cancer (28,29).…”
Section: Discussionmentioning
confidence: 99%